Effects of Catalase on Growth Performance, Antioxidant Capacity, Intestinal Morphology, and Microbial Composition in Yellow Broilers - Tang, Minghong; Fang, Rejun; Xue, Junjing; Yang, Kaili; Lu, Yi (Frontiers in Veterinary Science, 2022)
Abstract The objective of this experiment was to study the effects of catalase (CAT) on growth performance, antioxidant capacity, intestinal morphology, and microbial composition of yellow broilers. Male Lingnan yellow broilers of 360 in the age of 1 day were randomly divided into control group (CON) (fed with a basic diet), R1 group (fed with basic diet+150 U/kg catalase) and R2 group (fed with basic diet+200 U/kg catalase). Each group had 8 replicates and 15 chickens in each replicate. The test is divided into the early stage (1-30 days) and the later stage (31-60 days). The results showed that:compared with the control group, groups R1 and R2 significantly (P<0.05) increased the weight gain and reduced (P<0.05) the ratio of feed to gain in the early and the whole stages; prominently highed (P<0.05) the concentration of total antioxidant capacity (T-AOC), the activities of CAT, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) in livers, the activities of CAT and GSH-Px in serum and CAT in jejunums in the early and the later stages; markedly highed (P<0.05) the villus height and the ratio of villus height to crypt depth of duodenum in the early and the later stages, the villus height and the villus height:crypt depth ratio of jejunum and ileum in the early stage, and significantly lowed (P<0.05) the crypt depth of duodenum (in the early and the later stages), jejunum and ileum (in early stage); memorably (P<0.05) increased the number of Total bacteria and Bacteroidetes in ceca, as well as the number of Lactobacillus in jejunums (P<0.05) on the 30th; significantly (P<0.05) increased the mRNA expression of junction adhesion molecule 2 (JAM2), mucin 2 (MCU2) and occlusal protein (Occludin) in the duodenum in the early stage, and increased (P<0.05) the mRNA expression of JAM2 in the jejunum in the later stage. Collectively, adding catalase (CAT) to the diet of yellow broilers can improve the growth performance and the antioxidant capacity, promote the integrity of intestinal morphology, optimize the composition of intestinal microorganisms, and upregulate the mRNA expression of tight junction protein.